2022
DOI: 10.3390/vaccines10020146
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Receive the COVID-19 Vaccine Booster Dose in a University Community in Italy

Abstract: This cross-sectional study, conducted in Naples (Italy) between 16 November and 6 December 2021, explored the willingness to receive the booster dose of the COVID-19 vaccine among a random sample selected from the list of those who had completed a primary vaccination series at the immunization center of a teaching hospital in Naples and the associated factors. Females had a significantly higher perceived risk of getting the SARS-CoV-2 infection, whereas those not-having a cohabitant were less worried. 85.7% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
91
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(126 citation statements)
references
References 30 publications
16
91
4
Order By: Relevance
“…Availability and accessibility to information on COVID-19 vaccination are crucial for the general population to help the individuals to make informed decisions and to have safe preventive behaviors. The positive effect of the information received from institutional and scientific sources on the correct perception of the severity of COVID-19 aligns well with the results from previous research which found that the exposure to these sources have a positive impact on the level of knowledge, on the attitudes, and on the acceptability of the vaccination than those exposed to other sources [ 12 , 17 , 18 , 19 , 20 , 21 ]. Moreover, it was particularly notable that the internet has become the third major source for respondents seeking vaccine information.…”
Section: Discussionsupporting
confidence: 88%
“…Availability and accessibility to information on COVID-19 vaccination are crucial for the general population to help the individuals to make informed decisions and to have safe preventive behaviors. The positive effect of the information received from institutional and scientific sources on the correct perception of the severity of COVID-19 aligns well with the results from previous research which found that the exposure to these sources have a positive impact on the level of knowledge, on the attitudes, and on the acceptability of the vaccination than those exposed to other sources [ 12 , 17 , 18 , 19 , 20 , 21 ]. Moreover, it was particularly notable that the internet has become the third major source for respondents seeking vaccine information.…”
Section: Discussionsupporting
confidence: 88%
“…Nowadays, a sizable body of literature, which found that receiving information and recommendation on vaccination from physicians is one of the most significant and consistent factors that influences the audience’s decision, supports this finding. Indeed, it has been revealed that trust in physicians, as in government organizations and scientific journals, positively influences the level of knowledge, the vaccine confidence, and the vaccine uptake [ 18 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A telephone survey was conducted from 14 December 2021 to 4 January 2022, as part of larger COVID-19 vaccination research enrolling different populations [ 9 , 11 , 17 , 18 ]. Using a simple random sampling method, a total of 890 children between the ages of 5 and 11 years with a chronic condition were recruited from the medical records of the outpatient Department of Pediatrics of a Teaching Hospital which is located in the city of Naples, southern part of Italy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the completion of the vaccination among priority groups, the mass vaccination program is now underway with the goal of including all eligible populations. However, similar to the initial phases of the vaccination program, hesitancy towards the third dose of vaccine still remains a concern for the health authority [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%